2022
DOI: 10.7759/cureus.28839
|View full text |Cite
|
Sign up to set email alerts
|

Vulnerability for Respiratory Infections in Asthma Patients: A Systematic Review

Abstract: Asthma is a non-communicable and long-term condition affecting children and adults. The air passages in the lungs become narrow due to inflammation and tightening of the muscles around the small airways. Symptoms of asthma are intermittent and include cough, wheeze, shortness of breath, and chest tightness. Asthma is very often underdiagnosed and under-treated in many regions, especially in developing countries. While many studies show that viral infections can precipitate asthmatic attacks, very few studies h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…Black and Hispanic children have higher rates of asthma and obesity than non-minority groups, which contribute to increased occurrence of infectious respiratory infections among these groups of children [ 21 , 23 , 26 , 27 ]. Other studies have also shown links between vulnerability to respiratory infections and chronic conditions such as asthma and obesity in adults and children [ 34 , 35 ]. As the rate of childhood chronic conditions continues to rise, it is imperative that interventions are developed to reduce or eliminate chronic conditions among these vulnerable populations in order to reduce the occurrence of respiratory infectious diseases and severe outcomes from those infections.…”
Section: Discussionmentioning
confidence: 99%
“…Black and Hispanic children have higher rates of asthma and obesity than non-minority groups, which contribute to increased occurrence of infectious respiratory infections among these groups of children [ 21 , 23 , 26 , 27 ]. Other studies have also shown links between vulnerability to respiratory infections and chronic conditions such as asthma and obesity in adults and children [ 34 , 35 ]. As the rate of childhood chronic conditions continues to rise, it is imperative that interventions are developed to reduce or eliminate chronic conditions among these vulnerable populations in order to reduce the occurrence of respiratory infectious diseases and severe outcomes from those infections.…”
Section: Discussionmentioning
confidence: 99%